NONTHERMAL EFFECTS OF MOBILE PHONE RADIATIONS ON HUMAN HEART RATE, BLOOD PRESSURE, AND SUGAR LEVEL - D, Basandrai; K, Dhami A; K, Bedi A (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: A single-blinded pilot study has been conducted to investigate the effect of cell phone radiation on the human heart.Â Methods: Experimental work has been conducted in Jalandhar-based hospital under the supervision of a cardiologist. During experimental work, electrocardiogram (ECG), blood pressure (BP) level, and sugar level have been examined before and after cell phone radiation exposure. For ECG analysis, the parameters such as heart rate, rhythm, mechanism, axis, P wave, PR interval, QRS complex, ST segment, T wave, and QT interval have been examined in the study. Results: No significant variations in the results of above-mentioned parameter has been observed before and after acute exposure of cell phones radiations by placing cell phone closer to heart. Conclusion: The result of this study concludes that mobile phone radiations do not interfere with any electrical activity of the human heart, BP, and sugar level in healthy individuals.